Investigación psicológica para el manejo del estrés en los niños originado por la pandemia del COVID-19 - Martínez Riofrío, Manuel Reinerio (My University, 2021)
Stress is considered a state of psychological study that greatly affects the different spheres of personal, social and work development. After the appearance of the Covid-19 pandemic, the mental health of people, especially minors, has suffered an emotional imbalance with alterations and psychological repercussions. The importance of psychological intervention for the management of stress caused by confinement measures, restrictions, social limitations or isolation, information not appropriate to their age, It has caused difficulty in concentration, emotional reactions, stress, fear of contagion and other psychological aspects that affect their mental health. The objective set for this research, to determine the psychological consequences that arose in children due to the Covid-19 pandemic. Based on integrative psychology as an intervention model due to the opportunity it offers when grouping theoretical models, among those used: Cognitive Behavioral psychology, which allows a self-analysis of irrational thoughts, the type of behavior and the appreciation of the reality that the subject is faced with the situation that generates significant discomfort, humanistic therapy that allows the management of subjectivity and conceives the human being as a potential integrated entity to face the problem situation and finally, we work with systemic family therapy, which provides psychological intervention, self-analysis of the existing dynamics, cohesion and adaptability of the family constellation. These currents present effective intervention techniques detailed in a therapeutic plan described at the end of the work.
El estrés es considerado un estado de estudio psicológico que afecta en gran medida las diferentes esferas de desenvolvimiento personal, social y laboral. Luego de la aparición de la pandemia Covid- 19, la salud mental de las personas, especialmente en los menores ha sufrido un desbalance emocional con alteraciones y repercusiones psicológicas. La trascendencia de la intervención psicológica para el manejo del estrés originado por las medidas de confinamiento, restricciones, limitaciones sociales o aislamiento, información no adecuada a su edad, ha ocasionado dificultad para la concentración, reacciones emocionales, estrés, miedo al contagio y demás aspectos psicológicos que repercuten en su salud mental. El objetivo trazado para esta investigación: determinar las consecuencias psicológicas que surgieron en los niños por la pandemia del Covid-19. Basado en la psicología integrativa como modelo de intervención por la oportunidad que brinda al agrupar modelos teóricos, entre los utilizados, la psicología Cognitivo Conductual, que permite realizar un auto análisis sobre los pensamientos irracionales, el tipo de conducta y la apreciación de la realidad que tiene el sujeto ante la situación que genera malestar significativo, la terapia humanista que permite el manejo de la subjetividad y concibe al ser humano como ente potencial integrado para afrontar la situación problémica y por último se trabaja con la terapia sistémica familiar, misma que brinda intervención psicológica, autoanálisis de la dinámica existente, cohesión y la adaptabilidad de la constelación familiar. Estas corrientes presentan técnicas de intervención eficaces detalladas en un plan terapéutico descrito al finalizar el trabajo.
Keywords: FACTOR ESTRESOR; INTERVENCION PSICOLOGICA; TERAPIA SISTEMICA FAMILIAR; PANDEMIA COVID-19